Correlates of physical activity in young people: A narrative review of reviews. Implications for physical education based on a socio-ecological approach (Correlatos de actividad física en jóvenes: Una revisión narrativa de revisiones. Implicaciones para - Martins, João; Marques, Adilson; Peralta, Miguel; Palmeira, António; Carreiro da Costa, Francisco (Retos, 2017)
School and physical education (PE) play an important role in promoting youth physical activity (PA). Although there is extensive evidence about the correlates of PA in youth, few studies summarize these findings and critically connect them to PE based on a socio-ecological approach. The purpose of this article was to perform a narrative review of systematic reviews and of systematic reviews of reviews about the correlates of PA for children and adolescents, and to identify practical implications to PE using a socio-ecological model as a framework. Reviews were identified from searches in Pubmed, PsycINFO, Sportdiscus, ERIC, Web of science databases from 2000 through 2016. Based on established criteria, 20 reviews and four reviews of reviews were analysed. Results were presented in tables and through a narrative synthesis. The main correlates of PA for children and adolescents were: sex (male), age (inverse association), self-efficacy, previous PA, time spent outside (children), parental support, and access to facilities/programs of PA. The implications for PE were critically analyzed around five emerging themes: (1) active PE, (2) learning focused PE and PA for life, (3) Motivational climate in PE and students’ psychosocial profiles, (4) Family and friends, and (5) comprehensive school PA promotion. Efforts to increase school and PE effectiveness by promoting active lifestyles require a comprehensive approach, and should be based on the design of PE and PA programs and the implementation of strategies that build on the main multilevel correlates of PA. Resumen. La escuela y la educación física (EF) desempeñan un papel importante en la promoción de la actividad física (AF) en la juventud. Aunque existe una amplia evidencia acerca de los correlatos de la AF en los jóvenes, pocos estudios resumen estos hallazgos y los vinculan críticamente a la EF basándose en un enfoque socio-ecológico. El propósito de este artículo fue realizar una revisión narrativa de revisiones sistemáticas y de revisiones sistemáticas de revisiones sobre los correlatos de la AF para niños y adolescentes, e identificar implicaciones prácticas para la EF, usando como marco un modelo socio-ecológico. Las revisiones se identificaron a partir de búsquedas realizadas en las bases de satos de Pubmed, PsycINFO, Sportdiscus, ERIC, y Web of science, de 2000 a 2016. Sobre la base de criterios establecidos, se analizaron 20 revisiones y cuatro revisiones de revisiones. Los resultados fueron presentados en tablas y mediante una síntesis narrativa. Los principales correlatos de la AF para niños y adolescentes fueron: sexo (masculino), edad (asociación inversa), autoeficacia, AF previa, tiempo pasado fuera (niños), apoyo de los padres y acceso a instalaciones/programas de AF. Las implicaciones para la EF fueron analizadas críticamente alrededor de cinco temas emergentes: (1) educación física activa, (2) aprendizaje centrado en la EF y la AF para la vida, (3) clima motivacional en la EF y perfiles psicosociales de los estudiantes, (4) familia y amigos, y (5) la promoción integral de la AF escolar. Los esfuerzos para incrementar la efectividad de la escuela y de la EF en la promoción de estilos de vida activos, requieren un enfoque integral y deben basarse en el diseño de programas EF y AF y la implementación de estrategias basadas en los principales correlatos a varios niveles de AF.